2019
DOI: 10.1088/1361-6501/ab2d63
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-oxide-coated fiber Bragg grating sensor for ethanol detection in petrol

Abstract: In this work, a study on a graphene oxide (GO)-coated fiber Bragg grating (FBG) sensor for ethanol detection in petrol is reported. The fiber Bragg gratings (FBGs) used in the present experiment were fabricated in-house using a high repetition rate (~5.5 kHz), with frequency-doubled copper vapour laser output radiation. The sensor head was made by partially removing the cladding of the FBG region using hydrofluoric acid (HF) and then coating a GO layer onto it. This GO-coated etched FBG (EFBG) shows a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It was estimated that the sensor can detect ethanol concentration changes of 1.5% in gasoline–ethanol mixtures and distinguish temperature variations of 0.5 °C. Kumar et al recently utilised a GO-coated Etched FBG (EFBG) sensor for ethanol measurement in petrol [ 85 ]. When compared to an un-coated EFBG, the GO-coated etched FBG (EFBG) demonstrated a ten-fold increase in ethanol sensitivity.…”
Section: Optical Fibre Sensing Methodsmentioning
confidence: 99%
“…It was estimated that the sensor can detect ethanol concentration changes of 1.5% in gasoline–ethanol mixtures and distinguish temperature variations of 0.5 °C. Kumar et al recently utilised a GO-coated Etched FBG (EFBG) sensor for ethanol measurement in petrol [ 85 ]. When compared to an un-coated EFBG, the GO-coated etched FBG (EFBG) demonstrated a ten-fold increase in ethanol sensitivity.…”
Section: Optical Fibre Sensing Methodsmentioning
confidence: 99%
“…Their results displayed as the concentration of Ethanol in water from 0 % to 100 % is better assessed measuring the change in absorbance with the thickest gold layer. Recently, Kumar et al [25] analyzed a graphene oxide-coated FBG for Ethanol detection in petrol. This sensor was manufactured covering a partially chemical etched FBG with a layer of an oxidize graphite powder by means of a drop casting technique.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the technique used to synthesize the GO solution also have been compared by investigating few works [9][10][11] and it is found that the work by Ridebi et al [11] have performed an easy and simple dip coating technique. The method has been conducted by dipping the fiber in the 200 µL GO aqueous solution at a constant speed.…”
Section: Introductionmentioning
confidence: 99%